Odpowiedzi

2010-02-10T16:10:42+01:00
A) -2(a-3b)+4(b-2a)-3(-5a+3b)= -2a+6b+4b-8a+15a-9b=5a+b dla a=-1, b=-4
5a+b=5*(-1)+(-4)=-5-4=-9

b) 3(x-5x+2)-4(3+2x+x)=3x-15x+6-12-8x-4x=-8x-6 dla x=-2
-8x-6=(-8)*(-2)-6=16-6=10

c) 2(-2x+5x-1)-5(2-x-x)=-4x+10x-2-10+5x+5x=16x-12 dla x=-1
16x-12=16*(-1)-12=-16-12=-28


Proszę...:]
1 5 1
Najlepsza Odpowiedź!
2010-02-10T19:56:29+01:00
A) -2(a-3b)+4(b-2a)-3(-5a+3b)= -2a+6b+4b-8a+15a-9b=5a+b dla a=-1, b=-4
5a+b=5*(-1)+(-4)=-5-4=-9

b) 3(x-5x+2)-4(3+2x+x)=3x-15x+6-12-8x-4x=-8x-6 dla x=-2
-8x-6=(-8)*(-2)-6=16-6=10

c) 2(-2x+5x-1)-5(2-x-x)=-4x+10x-2-10+5x+5x=16x-12 dla x=-1
16x-12=16*(-1)-12=-16-12=-28